ANALISIS FENOMENA I’JAZ AL – BAYANI DALAM NAZM (SUSUNAN) AL- QUR’AN - M. Rivan Febriansyah Harahap; M. Habib AlHabsyi, Harun Al Rasyid (Adisam Publisher, 2024)
The aim of this research is to describe the phenomenon of ljaz Al-Bayani in the Al- Quran, which refers to the special features of language and word formation which are considered as evidence of the divinity of the Al-Quran in Islamic beliefs. This concept involves two important aspects: first,